Pembinaan Kecerdasan Spiritual Siswa di Pondok Pesantren Thawalib Tanjung Limau - Annisaul Khairat; Vicky Rizki Febrian (LP2M STIT Palapa Nusantara, 2023)
The aims of this study were (1) to find out the planning process for fostering students' spiritual intelligence; (2) knowing the process of training students' spiritual intelligence training at the Thawalib Islamic Boarding School Tanjung Limau. This research is a field research with a qualitative approach to discover and re-describe what is happening in the field in relation to fostering the spiritual intelligence of students at the Thawalib Islamic Boarding School Tanjung Limau. The sources of information for this research were the Head of the Thawalib Islamic Boarding School, the Head of the Thawalib Islamic Boarding School MTsS, Madrasah Caregivers/Assistant, students and curriculum representatives. Data collection techniques used were observation, interviews, documentation and confirmation of the correctness of the material, the researchers used triangulation. The Thawalib Islamic Boarding School implements spiritual intelligence based on a study on the management of the development of students' spiritual intelligence conducted by the author at the Thawalib Islamic Boarding School Tanjung Limau, Tanjung Limau, Tanah Datar Regency. the development of students, which can be seen from the management process carried out: (1) Planning to develop the spiritual intelligence of the Tanjung Limau Thawalib Islamic Boarding School students is carried out through Tapak Suc-based extracurricular activities, the art of reading the Qur'an and Tahfidz, as well as daily routine activities, weekly and yearly. activities (2) )Implementation of Santri's Spiritual Intelligence Development at the Thawalib Tanjung Limau Tahfidz Islamic Boarding School which is carried out every Tuesday to Thursday, implementation of holy sites outside the curriculum forms spiritual and spiritual intelligence of students, extracurricular implementation of the art of reading the Qur'an including implementation with using the Tallaqi method.